2020
DOI: 10.3389/fmolb.2020.599101
|View full text |Cite
|
Sign up to set email alerts
|

Lack of a Clear Behavioral Phenotype in an Inducible FXTAS Mouse Model Despite the Presence of Neuronal FMRpolyG-Positive Aggregates

Abstract: Fragile X-associated tremor/ataxia syndrome (FXTAS) is a rare neurodegenerative disorder caused by a 55–200 CGG repeat expansion in the 5′ untranslated region of the Fragile X Mental Retardation 1 (FMR1) gene. FXTAS is characterized by progressive cerebellar ataxia, Parkinsonism, intention tremors and cognitive decline. The main neuropathological hallmark of FXTAS is the presence of ubiquitin-positive intranuclear inclusions in neurons and astrocytes throughout the brain. The molecular pathology of FXTAS invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Yet although these unmethylated Fmr1 hs341 mice experience molecular perturbations that closely resemble the FXTAS/FXPOI premutation (elevated Fmr1 transcript levels and reduced FMRP protein), they do not appear to exhibit any clear motor defects expected of FXTAS. A larger behavioral cohort may better determine whether Fmr1 hs341 displays any neurophysiological symptoms of FXTAS; however, existing data on motor deficits in knock-in mouse models of FXTAS are limited and occasionally conflicting ( Van Dam et al, 2005 ; Qin et al, 2011 ; Hunsaker, 2013 ; Foote et al, 2016 ; Haify et al, 2020 ). It is worth noting that FXTAS typically emerges after 50 years of age, so it is possible that these neurodegenerative symptoms will appear in Fmr1 hs341 mice of a more advanced age than used in this study (see “When are mice considered old?” from The Jackson Laboratory; https://www.jax.org/news-and-insights/jax-blog/2017/november/when-are-mice-considered-old ).…”
Section: Discussionmentioning
confidence: 99%
“…Yet although these unmethylated Fmr1 hs341 mice experience molecular perturbations that closely resemble the FXTAS/FXPOI premutation (elevated Fmr1 transcript levels and reduced FMRP protein), they do not appear to exhibit any clear motor defects expected of FXTAS. A larger behavioral cohort may better determine whether Fmr1 hs341 displays any neurophysiological symptoms of FXTAS; however, existing data on motor deficits in knock-in mouse models of FXTAS are limited and occasionally conflicting ( Van Dam et al, 2005 ; Qin et al, 2011 ; Hunsaker, 2013 ; Foote et al, 2016 ; Haify et al, 2020 ). It is worth noting that FXTAS typically emerges after 50 years of age, so it is possible that these neurodegenerative symptoms will appear in Fmr1 hs341 mice of a more advanced age than used in this study (see “When are mice considered old?” from The Jackson Laboratory; https://www.jax.org/news-and-insights/jax-blog/2017/november/when-are-mice-considered-old ).…”
Section: Discussionmentioning
confidence: 99%
“…However, measurements of ovarian dysfunction (FSH levels) and pituitary-adrenal dysfunction (prolactin, cortisol and ACTH levels) were not correlated with scores in the FXTAS motor rating scale in PM women [91], suggesting that endocrine and motor alterations in PM carriers do not have a simple relationship. Finally, no association has been observed between CGG repeats in the normal range and reproductive parameters (including FSH and AMH levels) [126], but there are some indications regarding high levels of FSH in cases bearing intermediate CGG sizes (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and fecundity problems and amenorrhea [115], an observation that deserves further confirmation.…”
Section: Endocrine Biomarkers In Premutation Carriersmentioning
confidence: 95%
“…Evidence for FMRpolyG toxicity has been collected from Drosophila and mouse models expressing different variants of engineered FMRpolyG aimed at enhancing or precluding such toxicity [42,48]. However, a recent study suggested that the appearance of FMRpolyG in neuronal intranuclear inclusions is not sufficient per se to trigger a clear phenotype in an inducible mouse model [49]. This is in contrast with the results obtained in a cellular model specifically designed to express the FMRpolyG in the absence of a CGG mRNA-dependent phenotype, in which cell viability was compromised and the nuclear lamina architecture was disrupted [50].…”
Section: Production Of Fmrpolyg Peptidesmentioning
confidence: 99%
“…Several transgenic driver lines have been used to drive the expression of this expanded repeat RNA in a ubiquitous or cell- or tissue-specific manner. These driver lines include the heterogeneous nuclear ribonucleoprotein-reverse tetracycline transactivator (hnRNP-rtTA), prion protein-reverse tetracycline transactivator (PrP-rtTA) and Ca 2+ /calmodulin-dependent protein kinase IIA-reverse tetracycline transactivator (CamKII-α-rtTA) ( Haify et al, 2020 ; Hukema et al, 2014 , 2015 ).…”
Section: Inducible and Cell- And Tissue-specific Fxtas Modelsmentioning
confidence: 99%